DETERMINATION OF VITAMIN C (ASCORBIC ACID) FROM Annona squamossa AND Valvet tamarind FRUITS - ABDULMUMIN, U.; IDRIS, B.; BELLO, A.; BAGNA, E.A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
This research was designed to compare two methods for determination of vitamin C (Ascorbic acid) content in Annona squamosa peel and pulp as well as in Velvet tamarind pulp. Vitamin C content of fresh fruit parts were determined by titrimetric and spectrophotometric methods using potassium permanganate as chromogenic reagent. Absorbance was measured spectrophotometrically at 530nm. The titration method was carried out using iodometric backtitration. The results obtained from the study revealed that there was significant difference between the two methods and the higher vitamin C content was recorded in Annona squamosa. Both samples could therefore be used to supplement vitamin C daily intake requirements.